Multimodal Imaging Does Not Delay Intravenous Thrombolytic Therapy in Acute Stroke - Salottolo, K.M.; Fanale, C.V.; Leonard, K.A.; Frei, D.F.; Bar-Or, D. (American Journal of Neuroradiology, 2011)
BACKGROUND AND PURPOSE: Patients with acute ischemic stroke require immediate medical treatment, and a CT to rule out hemorrhage is required before tPA. We adapted our protocol to include multimodal CT: unenhanced CT, CTA, and PCT. The purpose of this study was to determine whether multimodal CT imaging delays initiation of IV tPA beyond 60 minutes from hospital arrival. MATERIALS AND METHODS: All patients admitted during 3 years through the ED with a stroke alert and time from symptom onset to hospital arrival <2.5 hours were included. We examined 2 subgroups (multimodal CT versus unenhanced CT) to determine whether multimodal CT delayed tPA administration. Logistic regression was used to identify variables that predicted tPA within 60 minutes. RESULTS: There were 123 patients in the analysis, including 108 patients who were examined with multimodal CT. The median time from arrival to tPA was 56 minutes and was shorter for patients examined with multimodal CT (55 versus 78 minutes, P = .02). After adjustment, variables that were associated with tPA administration within 60 minutes included prehospital stroke alert (OR = 3.47, P = .03), time to CT (OR = 0.94, P = .01), and onset-to-arrival time (OR = 1.02, P = .04). There was no statistically significant difference in the odds of receiving timely tPA for multimodal versus unenhanced CT (OR = 3.99, P = .07). CONCLUSIONS: In our single-center experience, the use of multimodal imaging in patients with acute stroke did not delay IV tPA beyond 60 minutes. Further study is needed to assess the feasibility of the routine use of multimodal imaging in the acute stroke setting. CIconfidence intervalCTACT angiographyEDemergency departmentEMSemergency medical servicesIAintra-arterialIQRinterquartile rangeIVintravenousNIHSSNational Institutes of Health Stroke ScaleNINDSNational Institute of Neurological Disorders and StrokeORodds ratioPCTperfusion CTSMCSwedish Medical CentertPAtissue plasminogen activator